Penerapan Nilai Nilai Pendidikan Karakter pada Mata Kuliah Maharatul Kalam - Albarra Sarbaini; Aan Hasanah (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2021)
This study aims to incorporate the values ​​of character education into the Maharah Kalam course so that students are not only able to master and speak Arabic fluently, even more than that, they are able to apply the values ​​of character education and ingrained it in everyday life. The research method used in this research is a qualitative method. Data collection techniques use observation, interviews (student lecturers), and documentation. The subjects of this study were Maharatul Kalam lecturers and Arabic Language Education Students of IAIN Metro Lampung. The data in this study were obtained by researchers from the observation process carried out on PBA students and Maharatul Kalam lecturers. Researchers made direct observations of the learning process. The data analysis technique used is data reduction, data collection, data presentation, and verification and conclusion. Data validation using triangulation (combined). The results of the study have shown that the IAIN Metro PBA Study Program has been able to integrate character values ​​in Arabic learning, especially Maharatul Kalam, including through: (1) adjusting character values ​​with the lecture material being taught, (2) inserting character values ​​or trying to take lessons in each lecture materials, (3) conveying character values ​​through the learning methods used, and (4) planting and applying the value of character education in the daily life of students.